Pengembangan Sistem Informasi Pencatatan Pengujian Relay Proteksi Pada Sub-Unit Basecamp PT. PLN (Persero) Transmisi Jawa Bagian Timur dan Bali Menggunakan Metode Waterfall - Shiella Regina Febriyanisa; Ismiarta Aknuranda; Yusi Tyroni Mursityo (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
PLN (Persero) is a state-owned enterprise engaged in the electricity sector. PT. PLN is divided into several units, one of them is the East Java and Bali Transmission units. Each transmission unit has a basecamp in which there is a division of protection, meter and automation maintenance. This division is responsible for maintaining shutdown testing based on the type of protection relay using a protection relay test equipment. The test results are recorded on the testing form, then the data entered into Microsoft Excel. After all the test results are complete, made a report, printed and examined by the supervisor for approval. Based on the problems that have been described, a tool is needed to help the process of recording and reporting to be more effective and efficient with information systems. The information system development method used is waterfall with the stages of requirements analysis, design, implementation and testing. Implementation results is an information system for recording web-based protection relay testing. This system allows officers to add data and print test results, supervisors can verify and the parties concerned can directly check the results of the test. Furthermore, the implementation results are tested by validation testing which shows valid test results according to the requirements that have been identified, browser compatibility testing shows there are 17% error issues and the system can be run on several browsers without any obstacles found.